Unearthing Financial Wisdom Exploring the Factors Shaping Financial Literacy among Agribusiness Entrepreneurs in Zimbabwe - Gumbo, Lilian; Marimuthu, Ferina; Vengesai, Edson (LPPM of NAROTAMA UNIVERSITY, 2024)
Agribusiness serves as the cornerstone of the Zimbabwean economy, with a significant portion of the population relying on agricultural-related pursuits for sustenance. However, the concerning financial practices exhibited by agribusiness entrepreneurs, coupled with lackluster sectoral performance, present pressing issues. These issues manifest as pronounced instances of financial exclusion, loan defaults, and diminished productivity within the sector. The primary focus of this study was to assess the financial literacy of agribusiness entrepreneurs and elucidate the principal determinants of this literacy, employing the theoretical framework of the lifecycle hypothesis. The research design employed was explanatory in nature, involving the collection and subsequent quantitative analysis of data via questionnaires. The study encompassed a population of 172,221 agribusiness farmers hailing from five distinct districts in Zimbabwe, namely Mutare, Mt Darwin, Mutoko, Gweru, and Masvingo. To ensure a representative sample, a sample size of 623 was calculated utilizing the Slovin formula. The research outcomes unveiled an overall deficiency in financial literacy within the agribusiness sector, particularly pronounced among women, individuals with low incomes, those possessing limited educational attainment, and those supporting multiple dependents below the age of 18. As a crucial recommendation, the study advocates for the implementation of mandatory financial literacy courses at both the primary and secondary education levels. Such an intervention could contribute significantly to addressing the identified shortcomings in financial literacy among agribusiness entrepreneurs and subsequently foster more prudent financial behaviors within the sector.